2000
DOI: 10.1104/pp.124.3.991
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Induced 1→3-β-d-Glucan Inhibits Cell-to-Cell Trafficking of Molecules through Plasmodesmata. A New Mechanism of Aluminum Toxicity in Plants

Abstract: Symplastic intercellular transport in plants is achieved by plasmodesmata (PD). These cytoplasmic channels are well known to interconnect plant cells to facilitate intercellular movement of water, nutrients, and signaling molecules including hormones. However, it is not known whether Al may affect this cell-to-cell transport process, which is a critical feature for roots as organs of nutrient/water uptake. We have microinjected the dye lucifer yellow carbohydrazide into peripheral root cells of an Al-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
150
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(156 citation statements)
references
References 76 publications
1
150
0
5
Order By: Relevance
“…Callose formation has been induced in the apical root cells of aluminum-sensitive maize cultivars (Sivaguru et al, 1999) and Arabidopsis mutants with increased sensitivity to aluminum (Larsen et al, 1996). A study using immuno-fluorescence and immuno-electron microscopic techniques combined with monoclonal antibodies against callose (Sivaguru et al, 2000) showed that aluminum-sensitive wheat root growth inhibition was closely associated with the blockage of plasmodesmata (cytoplasmic channels responsible for the intercellular movement of water, nutrients and for signaling) by callose deposition under aluminum stress, which could effectively block symplastic transport and communication in higher plants. One of the key enzymes acting in callose formation is callose synthase, which showed high similarity with genes in the SUCEST database.…”
Section: Discussionmentioning
confidence: 99%
“…Callose formation has been induced in the apical root cells of aluminum-sensitive maize cultivars (Sivaguru et al, 1999) and Arabidopsis mutants with increased sensitivity to aluminum (Larsen et al, 1996). A study using immuno-fluorescence and immuno-electron microscopic techniques combined with monoclonal antibodies against callose (Sivaguru et al, 2000) showed that aluminum-sensitive wheat root growth inhibition was closely associated with the blockage of plasmodesmata (cytoplasmic channels responsible for the intercellular movement of water, nutrients and for signaling) by callose deposition under aluminum stress, which could effectively block symplastic transport and communication in higher plants. One of the key enzymes acting in callose formation is callose synthase, which showed high similarity with genes in the SUCEST database.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the formation of callose deposits at the neck region of PD leading to reduced size exclusion limits or PD closure has frequently been described as a specific response of plants to different abiotic and biotic stresses, including wounding, metal toxicity, and microbial infection (Enkerli et al, 1997;Iglesias and Meins, 2000;Sivaguru et al, 2000;Roberts and Oparka, 2003). For instance, enhanced callose accumulation was observed in membranes and PD of pea roots in response to aluminum treatment, leading to the blockage of symplastic transport and inhibition of root elongation (Sivaguru et al, 2000). Interestingly, callose formation was strongly correlated with aluminuminduced oxidative damage to membrane lipids and changes in intracellular calcium homeostasis, suggesting a mechanistic link between lipid peroxidation and callose synthesis (Jones et al, 1998;Yamamoto et al, 2001).…”
Section: Callose Deposition In the Vascular Tissue Correlates With Tomentioning
confidence: 99%
“…Callose deposition at Pds is stimulated by physical and physiological stresses (Hughes and Gunning, 1980;Beffa and Meins, 1996;Iglesias and Meins, 2000;Sivaguru et al, 2000;Rinne et al, 2005;Ueki and Citovsky, 2005;Maeda et al, 2006) and is proposed to provide a mechanism for regulating Pd flux (Botha and Cross, 2000;Iglesias and Meins, 2000;Levy et al, 2007a). Hence, for example, plants with reduced accumulation of the glycolytic enzyme 1,3-b-glucanase had increased callose accumulation and a reduction in the experimental molecular size exclusion limit.…”
Section: Introductionmentioning
confidence: 99%